Voltage Mode Pulse Width Modulator Using Single Operational Transresistance Amplifier - Rajeshwari Pandey; Neeta Pandey; Sajal K. Paul (Journal of Engineering)
This paper presents a voltage mode pulse width modulator (PWM) using single operational transresistance amplifier (OTRA). The proposed PWM consists of a relaxation oscillator output which is modulated using modulating signal. PSPICE simulation results and experimental results have been included to verify the theoretical analysis.